Zajištění podnikatelského záměru dotací z fondů EU - Hlavatý, Adam (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Diplomová práce pojednává o problematice obnovitelných zdrojů energie a možnostech financování výroby elektrické energie ze slunečního záření pomocí fondů Evropské unie. Součástí práce je studie proveditelnosti a návrh žádosti pro čerpání finančních prostředků v rámci programu Eko-Energie, jako jednoho z možných zdrojů financování, který by značně podpořil rentabilitu projektu.

The Master’s thesis deals with the renewable resources of energy and possibilities of funding of solar electrical power production from European union funds. The thesis also contains the feasibility study and the concept of Eko-Energie program grant application form, which can help to gain the financial support for increasing the effectivity of the project.
Entrepreneurial project for grants from EU funds
Keywords: obnovitelné zdroje energie; dotace; Evropská unie; žádost o dotace; renewable resources of energy; grants; European union; call for funds